Монгол, англи зүйр цэцэн үгэнд эмэгтэй хүний үнэлэмж илрэх нь: Expression of Social values concerning women in Mongolian and English proverbs - Б., Мөнхцоож (Mongolian Studies, 2023)
The positive value for the women in Mongolian and English proverbs are expressed as hardworking, intelligent, as well as good adviser and helper for their husband. These qualities are considered more valuable than beauty. Negative value for the women are shown connecting and comparing with bad harmony of their animal husbandry and farm. The expressions “fizgig” and “querulous woman” are more frequently for saying women’s bad qualities in Mongolian proverbs but in English “as devil” and “difficult to trust” is used more. In both Mongolian and English proverbs which are said about women negative value is more than positive one. 62.3 percentage of 258 Mongolian proverbs, 69.7 percentage of 214 English proverbs are expressed as negative value.